TREATMENT OF STAPHYLOCOCCUS DISEASE IN PIGS USING A COMBINATION OF PROCABEN LA, SULPIDON, AND BIOSAN - Pyo, Paulus Oktavianus; Keray, Arkadius Suban; Dede, Matheus Mbele (Buletin Veteriner Udayana, 2025)
Traditional livestock management systems that lack proper sanitation can facilitate the emergence of infectious diseases, including those caused by Staphylococcus bacterial infections. Staphylococcus spp. can affect the respiratory tract and, if left untreated, may lead to livestock mortality, resulting in significant economic losses. This case study aims to document the treatment of Staphylococcus infections in pigs using Procaben LA, Sulpidon, and Biosan in Kupang City. The subject of this case was a four-month-old female pig with black coloration and an approximate body weight of 50 kg, originating from Kupang City. Observed clinical signs included reduced appetite, lethargy, pale pink conjunctiva and gingiva, and a capillary refill time (CRT) exceeding two seconds. Clinical examinations comprised assessments of rectal temperature, heart rate, respiratory rate, and systemic organ function. Hematological and bacterial identification tests were routinely conducted at the UPT Veterinary Laboratory, Provincial Livestock Service of East Nusa Tenggara. Bacterial culture on Mannitol Salt Agar (MSA) medium yielded colonies suspected to be Staphylococcus spp., characterized by round, elongated gray colonies with rough surfaces and clustered cocci morphology. Based on anamnesis, clinical examination, laboratory testing, and bacterial identification, the pig was diagnosed with a Staphylococcus infection. The treatment regimen included Procaben LA (4 mL), Sulpidon (5 mL), and Biosan (5 mL), all administered via intramuscular injection (IM). The therapy yielded positive outcomes, with notable improvements in the pig’s condition, restoration of appetite, and normalization of body temperature.